Woman Image in "Miss Jinjing Belanja Sampai Mati" Book - Yolanda Stellarosa (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2017)
Book of “Miss Jinjing Belanja Sampai Mati” or “Miss Carry Shops to Dies” explains about lifestyle, shopping world and woman leading to the emergence of Miss Jinjing’s icon for the spirit of shopaholic or shopping lovers. This research aims to reveal how Miss Jinjing Belanja Sampai Mati’s text book presents and reflects women image using of simulation imaginary model of Jean Baudrillard, and how the media is used as a means of capitalism legitimacy. This research uses a qualitative method. The research output concludes that women are as consumptive figures, connoisseur, and shopping lover. By having seen on simulation imaginary model of Jean Baudrillard, the form of image starts from representation, ideology, and simulation phases reflected in Miss Jinjing’s text book;  while the simulacra leading to hyperreality happens when the readers are brought into text persuasion. Media’s work in forming the image of consumptive women, shopping lovers and shopaholic is a reflection of capitalism identity. Media presents an excessive reality in its writing on lifestyle and shopping world for women to control and dominate so that women are able to be voluntary and even do in many ways to achieve hyperreality formed by capitalism system. Woman image established in this case, is no longer another thing than as commodity which is expected to be sold out to advertisers.